Effect of silty sand on the pre-passivation behaviour of 1Cr steel in a CO2 aqueous environment. (2nd April 2020) - Zhao, Yonggang; Liu, Wei; Banthukul, Wongpat; Fan, Yueming; Li, Xiaogang
ABSTRACT: The effect of silty sand on the pre-passivation behaviour of 1Cr steel in a CO2 aqueous environment was investigated by electrochemical measurements and immersion tests. The results indicated that the cathodic reaction was accelerated by silty sand at the initial corrosion stage, but it was inhibited during the late corrosion stage. The corrosion film presenting as one single layer structure under silty sand condition was mainly composed of Cr(OH)3, amorphous FeCO3, and silty sand. The content of Cr(OH)3 in the film with silty sand was lower and then higher than that without silty sand with increasing corrosion time. The film was separated by silty sand at the early stage and it was filled with silty sand during the late stage. In addition, the pre-passivation behaviour of 1Cr steel under silty sand condition was weakened and then strengthened compared to sand-free condition.